Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Exceeding expectations: economic forecasts and underreaction to macroeconomic announcements - Birz, Gene; Dutta, Sandip (SSRN Electronic Journal, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.fin

Economic forecasts, anchoring bias, and stock returns - Birz, Gene; Dutta, Sandip; Yu, Han (Financial Management, 2021)
By utilizing survey forecasts of macroeconomic statistics, we find that market participants’ expectations are not rational as they exhibit an anchoring bias. The forecasts systematically underpredict macroeconomic statistics and the forecast errors are predicted by past macroeconomic announcements. Most importantly, we find that the stock market does not see through this bias, that is, we find statistically significant stock price effects of “anticipated” components of macroeconomic announcements. Investors overweight the importance of historical information and do not make sufficient adjustments after the arrival of new information. © 2021 Financial Management Association International
Keywords: dept.fin; peer-reviewed

Is good news good and bad news bad in the REIT market - Birz, Gene; Devos, Erik; Dutta, Sandip; Tsang, Desmond (Journal of Real Estate Portfolio Management, 2021)
Keywords: dept.fin; peer-reviewed

Ex-ante performance of REIT portfolios - Birz, Gene; Devos, Erik; Dutta, Sandip; Nguyen, Khoa; Tsang, Desmond (Review of Quantitative Finance and Accounting, 2022)
The Real Estate Investment Trust (REIT) market has become an increasingly important vehicle for alternative investment for equity investors. While existing research examining the cross-section of REIT returns usually employs standard risk factors in the in-sample models, it can only show the ex-post performance of REIT portfolios. The goal of our paper is to examine the ex-ante performance of REIT portfolios (i.e., the ability of investors to earn abnormal returns in real time). We employ the out-of-sample methodology of Cooper, Gutierrez, and Marcum (2005), and show that ex-ante performance of REIT portfolios is rather weak. For about half of our 19-year sample over the period of 1999 to 2017, the portfolio performances of REITs chosen ex-ante do not beat the performances of the FTSE-NAREIT or the CRSP Equal-Weighted index. After adjusting for transaction costs, the REIT portfolios significantly further underperform their benchmarks. Overall, our findings suggest that the market is relatively efficient in the REIT sector, and it is difficult for investors to devise trading strategies that improve the ex-ante performance of REIT portfolios, based on standard risk factors.
Keywords: Abnormal returns; Out-of-Sample; Portfolio management; Predictability; REITs; Real estate; dept.fin; peer-reviewed